IMPLEMENTASI KURIKULUM NASIONAL DI TENGAH TANTANGAN SUMBER DAYA MANUSIA DAN INFRASTRUKTUR - Rahmania, Cici Aulia; Syahira, Khadijah Khansa; Alfiyyah, Ravina Azhar; Iskandar, Sofyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The curriculum is a structured educational planning aimed at the development of character and the improvement of the quality of life of students in line with the needs of society. In the lesson, the curriculum encompasses goals, materials, methods, and content as a guideline to achieve educational objectives. Curriculum renewal is crucial for making the learning process more effective and aligned with the developments in knowledge and technology. One significant reform in Indonesia is the introduction of the Merdeka Belajar Curriculum by the Ministry of Education and Culture in 2021, which provides freedom for schools to determine learning materials according to the potential and needs of students. However, the implementation of the Merdeka Curriculum faces several challenges, including whether schools are ready for the application of this curriculum. The research method used is literature study with a qualitative approach. Data collection is carried out through a systematic review of various sources such as books, scientific articles, journals, and official documents related to the curriculum and its implementation. The data obtained is analyzed descriptively to describe and interpret various issues that arise in the implementation of the Merdeka Curriculum and the efforts of curriculum renewal in Indonesia. This research aims to delve deeper into the problems that arise in the implementation of the Merdeka Learning Curriculum in Indonesia so that it can provide solutions for its implementation.